Newton's law of cooling

T(t)= Tm + (To-Tm)e^-kt, k >0\
Evaluate T(0). Simplify and explain the result

I'm very confused on how to do this, i think i will be able to explain the result but if you could help me simplify this that would be great, Thank you very much.

1 answer

Tm is the final temp after a long time as you can see from the equation. This is normally the temperature in the surrounding environment.
To is the starting temperature.

T(0) = Tm + To e^0 - Tm e^0
but e^0 is 1
so
T(0) = Tm + To - Tm
or
T(0) = To
or in other words the temp at T = 0 is the starting temp To
what else is new?